Fundamentalists toward democracy? Empirical analysis of fundamentalist attitudes and democratic attitudes in the Middle East - Hajizadeh, Kazem (SocietàMutamentoPolitica, 2015)
Huntington asks an important question in The Third Wave: if traditional Islamic values and beliefs have significantly retarded democratic progress in the past, to what extent are they likely to continue to do so in the future? Unlike Huntington’s work, this paper is primarily a micro-level analysis. It seeks to show how Muslim people interpret and evaluate Islam and democracy. So we want to attach more data to Huntington’s theory and wish to demonstrate that non-democratic political space and authoritarian governments in Muslim countries can’t be explained by the features of Islam; there are considerable reasons and facts to convince scholars to look for other factors. The results illustrate nearly all Muslims tend to Islam and democracy at the same time. It seems Large populations of moderate fundamentalists in Muslim countries are appearing who struggle to actualize Islamic teachings in a democratic political model.